A Nahdatul Ulama Values in Leadership At-Ma’arif School in Indonesia - Mufidah, Ulfi Amali (STIES ALIFA, 2021)
One of the efforts in instilling nu values is applied a theory and practice for school daily life education. NU is a religious organization that aims to preserve, develop and practice the islamic teachings of ahlusunnah wal jama'ah. The meaning of ahlusunnah wal jama'ah is the followers who cling to the Qur'an, al-Hadith, al-Ijma' and al-Qiyas. Every principal is leader, especially in Ma'arif schools they need to implement or practice the values, namely Tawasuth or I'tidal, Tawazun, Tasamuh and Amar Ma'ruf Nahi Mungkar in their school environment. The method used in this thesis is a qualitative descriptive method. The conclusions in this study proved the principal of Ma'arif school in Central Lampung applied the values of NU leadership both in and outside of the school environment by carrying out various kinds of activities which usually conducted by NU such as reading Tahlil, Istighazah, Shalawat etc., moreover every principal also applied an attitude of tolerance, fairness, teaching good things to all school residents. The purpose of in this research is to see the values of principal leadership in applying of cultural NU in Ma'arif school in Central Lampung, using a descriptive qualitative method, the data collection techniques consist of observation, interviews and documentation. The data would be analyzed, re-presented or reduced and finally the conclusions are drawn. Then the data is triangulated using source triangulation. The results of this study show that NU leadership values in Ma'arif school Central Lampung, are applied in extracurricular forms, such as: Tawasuth or I'tidal, and the implementation are fair attitudes that portrayed by the principal and directly implemented or exemplified to teachers and students. Tasamuh, is a tolerant attitude means the principal exemplifying the value to all school residents and human being without discriminating them. Tawazun is a balanced attitude where the principal exemplifies attitude of working everyday which is balanced by praying and worship. Amar Ma'ruf Nahi Mungkar, is an attitude to always doing good way and leaving the bad way, this exemplified in the behave of not insulting each other and instead of helping each other. In his leadership, the principal implemented NU cultural values to all school residents which implemented in his attitudes and behaviors.